International Comparisons of Productive Efficiency and Welfare - Donald Roy (Luxembourg Income Study (LIS), 1989)
The paper is based principally on the results of the International Comparison Project as of November 1989. It examines crude labor productivity, energy intensity, and the absolute level of real income of top and bottom quintiles in ten countries.
Keywords: 330